Iron homeostasis and macrophage polarization in pulmonary fibrosis: mechanisms and therapeutic perspectives - Luo, Minlan; Al-waqeerah, Ali; Gao, Lili (Frontiers in Immunology, 2026)
Idiopathic pulmonary fibrosis (IPF) is a chronic progressive and fatal interstitial lung disease with limited therapeutic options. Recent evidence highlights dysregulated iron metabolism in macrophages as a critical yet underrecognized driver of disease progression. Excess iron accumulation functions as a signaling cue that promotes macrophage polarization toward the pro-fibrotic M2 phenotype through pathways such as HIF-1α/IL-10/STAT6, contributing to aberrant tissue repair, myofibroblast activation, and excessive extracellular matrix (ECM) deposition. This review synthesizes current findings on the mechanistic interplay between iron homeostasis and macrophage phenotypic switching in IPF and evaluates emerging therapeutic strategies that target iron availability, including iron chelators, ferroportin modulators, and targeted nanocarrier delivery systems. While these approaches show promise, challenges remain regarding specificity, off-target effects, and systemic toxicity. By integrating mechanistic insights with translational advances, this review underscores the therapeutic potential of targeting the macrophage–iron axis and outlines how precision medicine-based interventions may offer novel avenues for effective IPF treatment.